TOXICOLOGICAL EFFECTS OF AFLATOXIN B1 ON GROWTH PERFORMANCE, HUMORAL IMMUNE RESPONSE AND BLOOD PROFILE OF JAPANESE QUAIL - S. Mahmood; M. Younus; A. Aslam; A. A. Anjum (Journal of Animal and Plant Sciences, 2017)
Toxic effects of Aflatoxin B1 on growth performance and humoral immune response against Newcastle disease Virus (NDV) vaccine were determined in Japanese quails. Quail chicks (n=300) were divided into five groups and each group was further sub-divided into two subgroups. One subgroup of each group was vaccinated with NDV vaccine to study the antibody response. Experimental diets were prepared by adding different levels of AFB1 i.e. 0.25mg/kg feed, 0.5mg/kg feed, 1 mg/kg feed and 2 mg/kg feed, and were offered to groups B, C, D and E respectively for 42 days, while group A was kept as control. Feed intake, body weight gain and feed conversion ratio were calculated on weekly basis. The Antibody titers of vaccinated quails were measured by haemagglutination inhibition test. Hematological parameters Erythrocyte sedimentation rate, Hb content, hematocrit and total leukocyte count were measured in AFB1 fed birds and were compared with the quails given basal diet. Results showed significant reduction (P≤0.05) in feed intake, weight gain and feed conversion ratio, when compared to control group. Moreover, anti-NDV antibody titre was significantly reduced (P≤0.05) in AFB1 fed groups. Hb content, hematocrit, and TLC had time and dose dependent decrease in AFB1 fed quails while ESR was increased significantly in AFB1 fed birds. This highlighted adverse effects of AFB1 on growth performance, humoral immune response and blood profile of quails.
Keywords: Aflatoxin B1; Japanese quails; growth performance; humoral immune response; blood profile